Immunization with tegument nucleotidases associated with a subcurative praziquantel treatment reduces worm burden following Schistosoma mansoni challenge - Henrique K. Rofatto; Bogar O. Araujo-Montoya; Patrícia A. Miyasato; Julio Levano-Garcia; Dunia Rodriguez; Eliana Nakano; Sergio Verjovski-Almeida; Leonardo P. Farias; Luciana C.C. Leite (PeerJ, 2013)
Schistosomiasis is a debilitating disease caused by flatworm parasites of the Schistosoma genus and remains a high public health impact disease around the world, although effective treatment with Praziquantel (PZQ) has been available since the 1970s. Control of this disease would be greatly improved by the development of a vaccine, which could be combined with chemotherapy. The sequencing of the Schistosoma mansoni transcriptome and genome identified a range of potential vaccine antigens. Among these, three nucleotidases from the tegument of the parasite, presumably involved in purinergic signaling and nucleotide metabolism, were proposed as promising vaccine candidates: an alkaline phosphatase (SmAP), a phosphodiesterase (SmNPP-5) and a diphosphohydrolase (SmNTPDase). Herein, we evaluate the potential of these enzymes as vaccine antigens, with or without subcurative PZQ treatment. Immunization of mice with the recombinant proteins alone or in combination demonstrated that SmAP is the most immunogenic of the three. It induced the highest antibody levels, particularly IgG1, associated with an inflammatory cellular immune response characterized by high TNF-α and a Th17 response, with high IL-17 expression levels. Despite the specific immune response induced, immunization with the isolated or combined proteins did not reduce the worm burden of challenged mice. Nonetheless, immunization with SmAP alone or with the three proteins combined, together with subcurative PZQ chemotherapy was able to reduce the worm burden by around 40%. The immunogenicity and relative exposure of SmAP to the host immune system are discussed, as key factors involved in the apparently synergistic effect of SmAP immunization and subcurative PZQ treatment.